Answer: x = - 7/12
Step-by-step explanation:
-3x + 2 - 5x - 7 = 4x + 2
=> -8x - 5 = 4x + 2
=> -12x = 7
=> x = - 7/12
Firstly, $3.99 × 5 = $19.95
Second, $2.75 × 5 = $13.75
Third, $2.70 × 3 = $8.1 (Since it is just $8.1 that won't make sense so we'd add a 0 so It's $8.10.)
Then we do the last one which is 13 × $0.89 = $11.57.
So now since we are done multiplying we can add it all up.
The answer is $53.37 when we finish adding it up.
and I don't know what A number sentence is sorry :(
I took a long time typing this :< I hope this helps though! :D
Step-by-step explanation:
x = father's age now
y = son's age now
x = 2y + 10
x - 20 = 5(y - 20) = 5y - 100
using the first in the second equation :
2y + 10 - 20 = 5y - 100
-10 = 3y - 100
90 = 3y
y = 30
x = 2y + 10 = 2×30 + 10 = 60 + 10 = 70
the father is now 70 years old, the son now 30 years old.
Answer:
10y^2-3xy+6x
Step-by-step explanation: